Development of physical fitness – gender differences and characteristics - Piotrowska, Katarzyna; Pabianek, Łukasz (Quality in Sport, 2019)
Physical activity, recreational sports as well as competitive sports effect the human body. Changes that occur under training are mainly connected to the adaptation process of body to specific form of activity. But on the other hand, changes that may be observed may lead to body functioning dysregulations that may affect health of sportsmen. Most of the changes are being observed mainly in the functioning of the female body system, despite the fact that they are not gender specific. In women, the undesirable effect of intensive training and heavy training loads may be inhibition of sexual maturation, withdrawal of the menstrual cycle and its irregularity, as well as resolution of the reproductive system function. That’s why the understanding of gender specific changes are so important for the sportsmen and trainers to understand what may be observed during training and what it may lead to. The aim of this work was to show the basic differences between gender physical fitness development observed during body development and physical training.